Persepsi Peternak tentang Penerapan Inseminasi Buatan di Tiga Sentra Sapi Potong di Indonesia - Mursyid Ma’sum; Aida Vitayala S Hubeis; Amiruddin Saleh; Budi Saharjo (Jurnal Penyuluhan, 2012)
The general objective of the research is to describe and analyze implementation of adopted artificial insemination (AI) innovation on slaughter cattle’s farmers. Specifically, is to describe and analyze the perception of slaughter cattle’s farmers on AI in the three locations of research. Locations of the research are Kecamatan Geger Kabupaten Bangkalan and Kecamatan Mantup Kabupaten Lamongan in East Java Province and Kecamatan Penebel Kabupaten Tabanan in Bali Province. This research was designed as a correlation descriptive survey by both quantitative and qualitative approach. The number of sample is 240 respondents -who is the acceptors of AI- and by approach of stratified random sampling method. Data collection was completed with questionnaires, interview and field observation. Kruskal-Wallis Test and U Mann-Whitney Test were applied to analyze the data sample. The result of the research showed that the perception of the farmers on most of AI’s aspects are significantly different among locations of the research, with the exception of the phenotipe (physical appearance) of breed cattle and the artificial insemination services by inseminators. To be suggested that socialization or extension on AI should be conducted by different approaches to fit the characteristic of internal and external and AI’s perception of the farmers.Keywords: Perception, artificial insemination